1993
DOI: 10.1115/1.2910727
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Transfer, Missing Pin, and Optimization for Cylindrical Pin Fin Arrays

Abstract: This paper reports an experimental investigation on the effects of interfin spacing, shroud clearance, and missing pin on the heat transfer from cylindrical pin fins arranged in staggered and in-line arrays. The interfin spacing in the span wise direction was so small that the pins were almost touching each other. It was found that the optimum interfin spacing in both spanwise and streamwise directions is 2.5 D regardless of both type of array and shroud clearance used. The effect of missing pin for various in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 17 publications
1
33
1
1
Order By: Relevance
“…Kemudian menurun kembali dengan kenaikan Sy/D. Sedangkan dari literatur [6,7] disebutkan bahwa perpindahan panas maksimum untuk susunan sirip pin silinder lurus (straight cylinder pin fin array) dicapai pada nilai Sy/D = 2,5.…”
Section: Perhitungan Faktor Gesekanunclassified
“…Kemudian menurun kembali dengan kenaikan Sy/D. Sedangkan dari literatur [6,7] disebutkan bahwa perpindahan panas maksimum untuk susunan sirip pin silinder lurus (straight cylinder pin fin array) dicapai pada nilai Sy/D = 2,5.…”
Section: Perhitungan Faktor Gesekanunclassified
“…They found that the area averaged heat transfer coefficient on the heated surface depends on the distances between pin-fins for both staggered and in-line arrays. Chyu et al [7] reported the heat transfer performance of pin-fin arrays in a cooling channel. The heat transfer rate was enhanced by at least a factor of two while introducing one of the pin fin arrays in the smooth channel, and the staggered pin fin arrays showed higher thermal performance than the in-line arrays.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the channel pressure drops decrease significantly with moderate heat transfer reductions by opening small gaps between the pin-tips and the channel end wall. Jubran et al [9] reported on an experimental investigation to study the effects of shroud clearance, optimum inter-fin spacing in both span wise and stream wise directions. In a study performed by Tahat et al [10] in a channel with rectangular cross section equipped with needle fins, the effects of the distance between fins, the space above them and their in-line and staggered arrangement on heat transfer were investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%